Lack of recovery from hepatic oxidative damage in rats treated with Nigerian bonny light crude oil (2012)
The use of Nigerian bonny light crude oil (BLCO) in the treatment of gastrointestinal disorders, burns, foot ulcers and reproductive capacity is a common practice in the southern part of Nigeria. Towards understanding the mechanism and the reversibility of hepatotoxicity induced by BLCO, adult male Wistar rats were orally administered with BLCO at 0, 50, 100 and 200 mg kg 1 for 21 days. One-half of the rats were sacrificed on day 22, whereas the remaining half stayed for an additional 21 days without treatment. Whereas the activities of antioxidant enzymes such as superoxide dismutase, catalase, glutathione S-transferase were significantly (p<0.05) increased, gamma glutamyl transferase activity was significantly decreased in a dose-dependent manner. The levels of glutathione, hydrogen peroxide and malondialdehyde were significantly elevated in BLCO-treated animals. In addition, hepatic degeneration was accompanied with elevation in serum aminotransferases activities without affecting bilirubin levels. Whereas most of the above-mentioned parameters were consistent in animals from withdrawal experiment, both total and conjugated bilirubin levels were significantly increased after 21 days of BLCO-treatment withdrawal. Taken together, BLCO-induced hepatotoxicity could be due to increased oxidative stress which was not reversible upon withdrawal of treatment within the time course of investigation in male rats.